Metal-doped zinc oxide quantum dot catalyst, preparation method and application thereof, and method for preparing synthesis gas from carbon dioxide

By using metal-doped zinc oxide quantum dot catalysts, the efficiency and proportional regulation problems of CO2 conversion into synthesis gas in the prior art are solved, and efficient catalytic and adjustable CO2 conversion effects are achieved.

CN119876992AActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311386183.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25
Estimated Expiration
2043-10-24

AI Technical Summary

Technical Problem

It is difficult for the prior art to achieve efficient catalytic conversion of CO2 into synthesis gas and regulate the proportion of synthesis gas within a large range.

Method used

The catalyst is prepared by a metal-doped zinc oxide quantum dot catalyst by solvothermal method. The radius of the oxidized state ion of the doped element is different from that of Zn2+, forming a solid solution, causing zinc oxide lattice distortion and promoting the activation of carbon dioxide.

Benefits of technology

It has achieved high catalytic reduction and selectivity, has significant activation effect on CO2, and can regulate the proportion of synthesis gas within a large range, which is conducive to the synthesis of downstream products of synthesis gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876992A_ABST
    Figure CN119876992A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrocatalytic CO2 reduction, and discloses a metal-doped zinc oxide quantum dot catalyst as well as a preparation method and application thereof. Based on the total weight of the catalyst, the metal-doped zinc oxide quantum dot catalyst contains 95-100 wt% of zinc oxide and 1-5 wt% of doped metal, and the zinc oxide and the doped metal exist in the form of a solid solution. The catalyst can be prepared by the following method: (1) dissolving a zinc salt and a metal salt in an alcohol solvent to obtain a mixed solution I; (2) reacting the mixed solution I with an alcohol solution of alkali to obtain a mixed solution II; and (3) mixing the mixed solution II with a solvent, and treating. The metal-doped zinc oxide quantum dot catalyst is used for preparing carbon monoxide through a carbon dioxide electrochemical reduction reaction, not only has higher catalytic activity and CO selectivity, but also can regulate and control the proportion of synthesis gas in a larger range, and is beneficial to synthesis of downstream products of the synthesis gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic CO2 reduction, and in particular to a metal-doped zinc oxide quantum dot catalyst, a preparation method thereof, and a method for preparing synthesis gas from carbon dioxide using the catalyst. Background Art

[0002] In recent years, in order to alleviate the global problem caused by excessive CO2 emissions, the effective conversion of CO2 into usable fuels and other value-added chemicals has become a research hotspot, which can not only reduce CO2 emissions, but also solve the energy shortage problem to a certain extent. Catalysts are the core of electrocatalytic reactions. Designing and preparing electrocatalysts with high activity, high selectivity and long life is the primary task in the field of CO2 electroconversion research. In recent years, many studies have focused on designing efficient electrocatalysts for converting CO2 to CO. Au and Ag are good catalysts for the electrocatalytic reduction of CO2 to CO. By designing different Au and Ag nanostructures, their activity in the hydrogen evolution reaction can be inhibited, thereby improving the selectivity for CO products. However, Au and Ag catalysts are precious metal catalysts with limited reserves and high prices, which limits their large-scale practical applications. Therefore, studying cheap and efficient non-precious metal catalysts is one of the key scientific issues to achieve low-cost electrocatalytic conversion of CO2 to CO.

[0003] CN112647099A discloses a method for preparing transition metal nanocatalysts by electrodeposition. First, K2SO4 or KHCO3 solution is added with transition metal insoluble salt (i.e., precursor) and oxide and stabilizer polyvinyl pyrrolidone (PVP) and ethanol to form a metastable mixed electrodeposition solution, and then pure copper sheet or carbon material is used as a carrier to immerse in the electrodeposition mixed solution, and electrodeposition is performed in a constant voltage mode. The invention utilizes the electric field formed during electrodeposition to adsorb metal insoluble salts and oxides to form metal nanostructures, which is suitable for transition metal elements such as Cu, Ag, Au, Zn, and Sn. The catalyst obtained by the invention has excellent performance and has good application prospects in electrocatalysis, photocatalytic reduction of CO2, and oxygen reduction.

[0004] CN104959135A discloses a nano zinc catalyst and a method for efficiently catalyzing CO2 reduction of CO based on the nano zinc catalyst. A nano zinc catalyst is grown on a zinc sheet substrate and is a nano sheet array structure, and nano particles are grown on the surface of the nano sheet. In an electrolytic cell separated into an anode tank and a cathode tank by a proton exchange membrane, the nano zinc catalyst electrode is used as a working electrode (cathode), a platinum sheet is used as an auxiliary electrode (anode), and a saturated calomel electrode is used as a reference electrode. Electrolyte solutions are respectively loaded in the anode tank and the cathode tank, CO2 is introduced into the cathode tank until saturation, and then CO2 is reduced at a constant potential under the condition of continuous introduction of CO2, and the potential control range in the constant potential reduction process is -1.4 to -1.8V.

[0005] Compared with bulk zinc electrodes, the obtained nanostructured zinc electrodes generally exhibit higher catalytic activity and CO selectivity, but they cannot achieve efficient catalytic conversion of CO2 into synthesis gas and simultaneously control the proportion of synthesis gas within a large range to facilitate the synthesis of downstream synthesis gas products. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem that the prior art cannot achieve efficient catalytic conversion of CO2 into synthesis gas and regulate the proportion of synthesis gas over a large range, and to provide a metal-doped zinc oxide quantum dot catalyst and its preparation method and application method for preparing synthesis gas from carbon dioxide.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a metal-doped zinc oxide quantum dot catalyst, wherein, based on the total weight of the metal-doped zinc oxide quantum dot catalyst, the metal-doped zinc oxide quantum dot catalyst contains 95-100wt% of zinc oxide and 1-5wt% of doped metal; and the zinc oxide and the doped metal exist in the form of a solid solution.

[0008] A second aspect of the present invention provides a method for preparing a metal-doped zinc oxide quantum dot catalyst, wherein the method comprises:

[0009] (1) dissolving a zinc salt and a metal salt in an alcohol solvent to obtain a mixed solution I;

[0010] (2) reacting the mixed solution I with an alcohol solution of an alkali to obtain a mixed solution II;

[0011] (3) The mixed solution II is mixed with a solvent and treated to obtain the metal-doped zinc oxide quantum dot catalyst.

[0012] The third aspect of the present invention provides a metal-doped zinc oxide quantum dot catalyst prepared by the preparation method of the second aspect of the present invention.

[0013] A fourth aspect of the present invention provides an application of a metal-doped zinc oxide quantum dot catalyst in an electrochemical reduction reaction of carbon dioxide.

[0014] A fifth aspect of the present invention provides a method for preparing synthesis gas from carbon dioxide, wherein the method comprises: in the presence of the metal-doped zinc oxide quantum dot catalyst provided by the present invention, electrochemically reducing carbon dioxide and water to obtain synthesis gas.

[0015] Through the above technical scheme, in the metal-doped zinc oxide quantum dot catalyst provided by the present invention, the oxidation state ion radius of the doped element is similar to that of Zn 2+ Different radii will cause the zinc oxide lattice distortion in the process of forming solid solution; and because the radii of the oxidation state ions of different doping elements are different, the degree of zinc oxide lattice distortion caused by doping zinc oxide is also different. The distortion of the zinc oxide lattice caused by the doping elements and the different degrees of distortion of the zinc oxide lattice caused by different doping elements can be seen from the XRD diagram of the product (such as Figure 1 As shown in the figure. Figure 1 It can be seen that based on the ion radius of the doping element oxidation state is larger than that of Zn 2+ The radius of the ZnO is large or small, and the distortion of the ZnO lattice causes the diffraction peak of the crystal plane to shift toward a larger angle or a smaller angle. In addition, depending on the doping elements, the diffraction peak corresponding to the same crystal plane shifts at different angles.

[0016] The metal-doped zinc oxide quantum dot catalyst of the present invention has an electronegativity of the oxidation state of the doped element similar to that of Zn 2+ The electronegativity of the doping elements is different. In the process of electrocatalytic CO2 reduction, this difference in electronegativity will cause electron transfer between the doping elements and the zinc element. The activation of carbon dioxide is an electron-requiring process. The electron transfer phenomenon can further promote the activation of carbon dioxide, thereby improving the catalytic activity. In addition, the electronegativity of different doping elements in oxidation state is different. When doping zinc oxide, the degree of electron transfer between different doping elements and zinc elements is also different, so the degree of promotion of carbon dioxide activation is also different. The oxidation state of the doping element and Zn 2+ The effect of the electronegativity difference between them on the selectivity of CO produced by electrocatalytic CO2 reduction and the regulation of the ratio of syngas can be found in Figure 3 , 4 , 5. From Figure 3 and 4It can be seen that under the same reaction conditions, when undoped ZnO quantum dots are used to electrocatalyze CO2 reduction to prepare CO, the maximum CO Faraday efficiency obtained is 78.4%, and the synthesis gas ratio can be adjusted between 0.9-3.7 by controlling the potential (between -0.7 and -1.4 Vvs. RHE); when Cu or Fe is doped with ZnO quantum dots, the selectivity of the doped ZnO quantum dot catalyst for CO is significantly reduced compared with ZnO quantum dots, and the maximum CO Faraday efficiency obtained is reduced to 68.4% or 64.9%, and the synthesis gas adjustment range is also narrowed to 0.6-2.2 or 0.8-1.8; when Co or Ni is doped with ZnO quantum dots, the selectivity of the doped ZnO quantum dot catalyst for CO is enhanced compared with ZnO quantum dots, and the maximum CO Faraday efficiency obtained is enhanced to 89.9% or 82.9%, and the synthesis gas adjustment range is also expanded to 1.3-9 or 1.2-4.8. It can be seen that the metal-doped zinc oxide quantum dot catalyst provided by the present invention not only effectively promotes the activation of carbon dioxide and achieves high catalytic reducibility and selectivity, but also simultaneously achieves the regulation of the proportion of synthesis gas within a larger range, which is beneficial to the synthesis of downstream products of synthesis gas.

[0017] In addition, the synthesis method adopted by the present invention has simple process, convenient operation, easy control, and does not use toxic reaction raw materials. It is an environmentally friendly green synthesis process. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the XRD pattern of zinc oxide quantum dots and zinc oxide quantum dots catalysts doped with different transition metals;

[0019] Figure 2 This is a high-magnification TEM photo of the zinc oxide quantum dot catalyst obtained in Comparative Example 1;

[0020] Figure 3 The Faraday efficiency and synthesis gas ratio of the zinc oxide quantum dot catalyst obtained in Example 1 for producing CO;

[0021] Figure 4 The Faraday efficiency and synthesis gas ratio of the doped zinc oxide quantum dot catalyst for producing CO obtained in Examples 1-4 are: a: Cu-ZnO, b: Ni-ZnO, c: Fe-ZnO, d: Co-ZnO;

[0022] Figure 5 This is a comparison chart of the Faraday efficiencies of CO produced by zinc oxide quantum dots obtained in Example 1 and different transition metal-doped catalysts obtained in Examples 1-4. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0025] The first aspect of the present invention provides a metal-doped zinc oxide quantum dot catalyst, wherein, based on the total weight of the metal-doped zinc oxide quantum dot catalyst, the metal-doped zinc oxide quantum dot catalyst contains 95-100wt% zinc oxide and 1-5wt% doped metal; and the zinc oxide and the doped metal exist in the form of a solid solution.

[0026] Non-precious metal-based catalysts are one of the important research systems for CO2 electroconversion. They are controllable and designable. By precisely controlling the size, composition, morphology and structure of nanocatalysts, and supplemented by instrumental characterization and other means, the catalytic mechanism of the catalyst during the reaction and the reaction paths of the different products obtained are studied, and efficient, highly selective and controllable CO2 electroconversion can be achieved. Zn, as a metal with abundant reserves on the earth, can also reduce CO2 to CO, but its activity and CO selectivity are relatively low compared with Au and Ag catalysts. In order to overcome these limitations, the first aspect of the present invention provides a metal-doped zinc oxide quantum dot catalyst.

[0027] In the metal-doped zinc oxide quantum dot catalyst of the present invention, the electronegativity of the oxidation state of the doping element is similar to that of Zn 2+ The electronegativity of the doping elements is different. In the process of electrocatalytic CO2 reduction, this difference in electronegativity will cause electron transfer between the doping elements and the zinc element. The activation of carbon dioxide is an electron-requiring process. The electron transfer phenomenon can further promote the activation of carbon dioxide, thereby improving the catalytic activity. In addition, the electronegativity of different doping elements in oxidation state is different. When doping zinc oxide, the degree of electron transfer between different doping elements and zinc elements is also different, so the degree of promotion of carbon dioxide activation is also different. The oxidation state of the doping element and Zn 2+ The effect of the electronegativity difference between them on the selectivity of CO produced by electrocatalytic CO2 reduction and the regulation of the ratio of syngas can be found in Figure 3 , 4 、5.

[0028] In some embodiments of the present invention, the doping elements are Cu, Fe, Co, or Ni respectively. Among them, the electronegativity order of the doping elements and Zn is Zn < Fe < Cu ≈ Co < Ni. Therefore, Zn all shows a tendency to gain electrons. In addition, if the electronegativity difference between elements is too small, the electron transfer ability between elements will not be strong enough, and the promotion effect on the electron gain activation of CO2 is not obvious; if the electronegativity difference between elements is too large, Zn will be too negatively charged, which is not conducive to the adsorption of CO2− intermediates. The influence of the doped metal elements on the zinc oxide quantum dots is also related to the adsorption ability of the doped metal to hydrogen and CO2 in addition to the electronegativity.

[0029] In the present invention, the method for preparing the metal-doped zinc oxide quantum dot catalyst can adopt the preparation method provided in the second aspect of the present invention.

[0030] According to the metal-doped zinc oxide quantum dot catalyst of the present invention, preferably, the crystal structure of the metal-doped zinc oxide quantum dot catalyst satisfies the following relationship: 0° < ∣A 110 -B 110 ∣ ≤ 1.8°, where A 110 and B 110 respectively represent the 2θ values of the diffraction peaks characterizing the (110) plane of ZnO in the XRD spectra of the metal-doped zinc oxide quantum dot catalyst and the XRD spectrum of zinc oxide obtained under the same XRD measurement conditions.

[0031] 0° < ∣A 002 -B 002 ∣ ≤ 1.8°, where A 002 and B 002 respectively represent the 2θ values of the diffraction peaks characterizing the (002) plane of ZnO in the XRD spectra of the metal-doped zinc oxide quantum dot catalyst and the XRD spectrum of zinc oxide obtained under the same XRD measurement conditions.

[0032] In some embodiments of the invention, preferably, the crystal structure of the copper-doped zinc oxide quantum dot catalyst satisfies the following relationships: A 110 -B 110 = 0.76°, A 002 -B 002 = 0.9°.

[0033] Preferably, the crystal structure of the iron-doped zinc oxide quantum dot catalyst satisfies the following relationships: A 110 -B 110 = 1.8°, A 002 -B 002 = 1.73°.

[0034] Preferably, the crystal structure of the cobalt-doped zinc oxide quantum dot catalyst satisfies the following relationship: 110 -B 110 =-0.74°, A 002 -B 002 =-0.54°.

[0035] Preferably, the crystal structure of the nickel-doped zinc oxide quantum dot catalyst satisfies the following relationship: 110 -B 110 =-1.44°, A 002 -B 002 =-1.24°.

[0036] According to the present invention, in order to distort the lattice of zinc oxide in the metal-doped zinc oxide quantum dot catalyst and generate electron transfer between the doping element and the zinc element, so as to ensure efficient, highly selective and controllable conversion of CO2 into CO during the electrocatalytic CO2 reduction process, preferably, in the metal-doped zinc oxide quantum dot catalyst, the doping metal is selected from transition metals, and is further preferably selected from one or more of copper, iron, cobalt and nickel.

[0037] In some embodiments of the invention, preferably, in the metal-doped zinc oxide quantum dot catalyst, the doping metal is copper, iron, cobalt or nickel.

[0038] According to the present invention, the average particle size of the metal-doped zinc oxide quantum dot catalyst is 3-15 nm, which can be measured by a laser particle size analyzer.

[0039] In some embodiments of the present invention, preferably, the average particle size of the metal-doped zinc oxide quantum dot catalyst is 10 nm.

[0040] In the present invention, the composition and structure of the metal-doped zinc oxide quantum dot catalyst can be determined by XRD and HRTEM testing methods, and can also be determined by the feeding amount of each material during the preparation process.

[0041] A second aspect of the present invention provides a method for preparing a metal-doped zinc oxide quantum dot catalyst, wherein the method comprises:

[0042] (1) dissolving a zinc salt and a metal salt in an alcohol solvent to obtain a mixed solution I;

[0043] (2) reacting the mixed solution with an alcohol solution of an alkali to obtain a mixed solution II;

[0044] (3) The mixed solution II is mixed with a solvent and treated to obtain the metal-doped zinc oxide quantum dot catalyst.

[0045] The present invention prepares the metal-doped zinc oxide quantum dot catalyst by a solvent thermal method. The electronegativity of the oxidation state of the doped metal is similar to that of Zn 2+ Different electronegativity of doping elements causes electron transfer between doping elements and zinc elements. The activation of carbon dioxide is an electron-requiring process. The electron transfer can further promote the activation of carbon dioxide, thereby improving the catalytic activity. In addition, the electronegativity of different doping elements in oxidation state is different. When doping zinc oxide, the degree of electron transfer between different doping elements and zinc elements is also different, so the degree of promotion of carbon dioxide activation is also different. The oxidation state of doping elements and Zn 2+ The effect of the electronegativity difference between them on the selectivity of CO produced by electrocatalytic CO2 reduction and the regulation of the ratio of syngas can be found in Figure 3 , 4 、5.

[0046] According to the present invention, in order to distort the lattice of zinc oxide in the metal-doped zinc oxide quantum dot catalyst and generate electron transfer between the doping element and the zinc element, so as to ensure efficient, highly selective and controllable conversion of CO2 into CO during the electrocatalytic CO2 reduction process, preferably, in the step (1), the mass ratio of zinc salt to metal salt is 1:0.0056-0.0754.

[0047] Preferably, in step (1), the zinc salt is Zn(CH3COO)2·2H2O.

[0048] Preferably, in step (1), the metal salt is selected from transition metal salts, and more preferably selected from one or more of copper acetate, iron acetate, cobalt acetate and nickel acetate.

[0049] In some embodiments of the invention, preferably, in step (1), the metal salt is copper acetate, iron acetate, cobalt acetate or nickel acetate.

[0050] In some embodiments of the invention, preferably, in step (1), the mass ratios of Zn(CH3COO)2·2H2O and the metal salt are 1:0.00563, 1:0.0151, 1:0.0133, 1:0.0664, respectively.

[0051] According to the present invention, in the preparation method, in order to accelerate the dissolution of zinc acetate and effectively prevent the solvent from evaporating too quickly, preferably, in the step (1), the dissolution temperature is 80-90°C.

[0052] In some embodiments of the present invention, preferably, in the step (1), the dissolution temperature is 80°C.

[0053] Preferably, the alcohol solvent is ethanol.

[0054] According to the present invention, in order to obtain small-sized ZnO quantum dots, preferably, in the step (2), the base is KOH; and the alcohol solution of the base is added dropwise, specifically at 2-10 mL / min.

[0055] According to the present invention, in the preparation method, in order to ensure sufficient reaction, preferably, in the step (2), the mass ratio of Zn(CH3COO)2·2H2O to KOH is 1:0.356-0.374.

[0056] More preferably, in step (2), the mass ratio of Zn(CH3COO)2·2H2O to KOH is 1:0.356.

[0057] Preferably, the reaction in step (2) is carried out in an ice bath.

[0058] According to the present invention, in the preparation method, in order to ensure that the prepared metal-doped zinc oxide quantum dot catalyst is completely precipitated, preferably, in the step (3), preferably, the solvent is n-hexane; and the volume ratio of the mixed solution II to n-hexane is 1:3-5.

[0059] More preferably, in step (3), the volume ratio of the mixed solution II to n-hexane is 1:3.

[0060] According to the present invention, in the preparation method, in step (3), the treatment is centrifugation at a speed of 4500-6000 r / min and vacuum drying.

[0061] In some embodiments of the present invention, preferably, in the step (3), the treatments are: centrifugation at a speed of 4500 r / min for 15 min, and vacuum drying at 60°C.

[0062] The third aspect of the present invention provides a metal-doped zinc oxide quantum dot catalyst prepared by the preparation method of the second aspect of the present invention.

[0063] A fourth aspect of the present invention provides an application of the metal-doped zinc oxide quantum dot catalyst of the present invention in an electrochemical reduction reaction of carbon dioxide.

[0064] A fifth aspect of the present invention provides a method for preparing synthesis gas from carbon dioxide, wherein the method comprises: in the presence of the metal-doped zinc oxide quantum dot catalyst of the present invention, electrochemically reducing carbon dioxide and water to obtain synthesis gas.

[0065] Under the same reaction conditions, when undoped ZnO quantum dots are used to electrocatalyze CO2 reduction to produce CO, the maximum CO Faraday efficiency obtained is 78.4%, and the synthesis gas ratio can be adjusted between 0.9-3.7 by controlling the potential (between -0.7 and -1.4 Vvs. RHE). The metal-doped zinc oxide quantum dot catalyst of the present invention is applied to the electrochemical reduction reaction of carbon dioxide to generate synthesis gas. When Cu or Fe is doped into ZnO quantum dots, the selectivity of the doped ZnO quantum dot catalyst for CO is significantly reduced compared with that of ZnO quantum dots, the maximum CO Faraday efficiency obtained is reduced to 68.4% or 64.9%, and the synthesis gas adjustment range is also reduced to 0.6-2.2 or 0.8-1.8; when Co or Ni is doped into ZnO quantum dots, the selectivity of the doped ZnO quantum dot catalyst for CO is enhanced compared with that of ZnO quantum dots, the maximum CO Faraday efficiency obtained is enhanced to 89.9% or 82.9%, and the synthesis gas adjustment range is also expanded to 1.3-9 or 1.2-4.8.

[0066] The following examples are used to illustrate the technical solutions of the present invention, wherein the raw materials and reagents used are all commercially available.

[0067] Zinc acetate, dihydrate, purity AR, purchased from Sinopharm Chemical Reagent Co., Ltd.

[0068] Copper acetate, purity 98.0%, purchased from Aladdin Reagent (Shanghai) Co., Ltd.

[0069] Ferric acetate, purity 98.0%, purchased from Aladdin Reagent (Shanghai) Co., Ltd.

[0070] Cobalt acetate, purity 98.0%, purchased from Aladdin Reagent (Shanghai) Co., Ltd.

[0071] Nickel acetate, purity 98.0%, purchased from Aladdin Reagent (Shanghai) Co., Ltd.

[0072] Potassium hydroxide, purity AR, purchased from Sinopharm Chemical Reagent Co., Ltd.

[0073] n-Hexane, purity 98.0%, purchased from Aladdin Reagent (Shanghai) Co., Ltd.

[0074] Comparative Example 1

[0075] Preparation of zinc oxide quantum dots

[0076] (1) Dissolve 5.50 g of Zn(CH3COO)2·2H2O in 150 mL of anhydrous ethanol solution and reflux with stirring at 80°C in a water bath for 2 h until the solution becomes colorless and transparent;

[0077] (2) Place the above solution in an ice bath, add 20 mL of 1.75 mol / L KOH-ethanol solution dropwise, and stir for 8 hours;

[0078] (3) The solution obtained in step (2) was mixed with n-hexane in a volume ratio of 1:3, and a large amount of white precipitate appeared. The mixture was centrifuged at 4500 r / min for 15 min and vacuum dried at 60° C. to obtain ZnO quantum dots.

[0079] The ZnO quantum dots were subjected to XRD measurement. Figure 1 The XRD diagram shown shows that in the crystal structure of ZnO quantum dots, the 2θ value of the diffraction peak of the ZnO (002) plane is 33.20°; the 2θ value of the diffraction peak of the ZnO (110) plane is 59.33°;

[0080] The ZnO quantum dots were subjected to high magnification TEM analysis. Figure 2 As shown in the TEM image, the particle size of ZnO quantum dots is about 5 nm.

[0081] Example 1

[0082] Preparation of copper-doped ZnO quantum dots (Cu-ZnO)

[0083] (1) Dissolve 5.50 g of Zn(CH3COO)2·2H2O and 0.031 g of copper acetate in 150 mL of anhydrous ethanol solution and reflux with stirring at 80°C in a water bath for 2 h until the solution becomes colorless and transparent;

[0084] (2) Place the above solution in an ice bath, add 20 mL of 1.75 mol / L KOH-ethanol solution dropwise, and stir for 8 hours;

[0085] (3) The solution obtained in step (2) was mixed with n-hexane in a volume ratio of 1:3, and a large amount of white precipitate appeared. The mixture was centrifuged at 4500 r / min for 15 min and vacuum dried at 60° C. to obtain copper-doped ZnO quantum dots.

[0086] The copper-doped ZnO quantum dots were subjected to XRD measurement. Figure 1 The XRD diagram shown shows that the 2θ value of the diffraction peak of the ZnO (002) plane in the crystal structure of the copper-doped ZnO quantum dots is 34.10°; the 2θ value of the diffraction peak of the ZnO (110) plane is 60.09°;

[0087] The copper-doped ZnO quantum dots were highly activated to effectively promote the activation of carbon dioxide, achieving high catalytic reducibility and selectivity. At the same time, the proportion of syngas can be regulated in a large range, which is beneficial to the synthesis of syngas downstream products. TEM analysis shows that the particle size of copper-doped ZnO quantum dots is about 10nm.

[0088] Example 2

[0089] Preparation of Iron-doped Zinc Oxide Quantum Dots (Fe-ZnO)

[0090] (1) Dissolve 5.50 g of Zn(CH3COO)2·2H2O and 0.083 g of ferric acetate in 150 mL of anhydrous ethanol solution and reflux with stirring at 80°C in a water bath for 2 h until the solution becomes colorless and transparent;

[0091] (2) Place the above solution in an ice bath, add 20 mL of 1.75 mol / L KOH-ethanol solution dropwise, and stir for 8 hours;

[0092] (3) The solution obtained in step (2) was mixed with n-hexane in a volume ratio of 1:3, and a large amount of white precipitate appeared. The mixture was centrifuged at 4500 r / min for 15 min and vacuum dried at 60° C. to obtain iron-doped ZnO quantum dots.

[0093] The iron-doped ZnO quantum dots were subjected to XRD measurement. The XRD pattern was consistent with Figure 1 Similarly, it can be seen that in the crystal structure of iron-doped ZnO quantum dots, the 2θ value of the diffraction peak of the ZnO (002) plane is 34.93°; the 2θ value of the diffraction peak of the ZnO (110) plane is 61.13°.

[0094] The iron-doped ZnO quantum dots were subjected to high-magnification TEM analysis, and the particle size of the iron-doped ZnO quantum dots was approximately 10 nm.

[0095] Example 3

[0096] Preparation of Cobalt-doped Zinc Oxide Quantum Dots (Co-ZnO)

[0097] (1) Dissolve 5.50 g of Zn(CH3COO)2·2H2O and 0.073 g of cobalt acetate in 150 mL of anhydrous ethanol solution and reflux with stirring at 80°C in a water bath for 2 h until the solution becomes colorless and transparent;

[0098] (2) Place the above solution in an ice bath, add 20 mL of 1.75 mol / L KOH-ethanol solution dropwise, and stir for 8 hours;

[0099] (3) The solution obtained in step (2) was mixed with n-hexane in a volume ratio of 1:3, and a large amount of white precipitate appeared. The mixture was centrifuged at 4500 r / min for 15 min and vacuum dried at 60° C. to obtain cobalt-doped ZnO quantum dots.

[0100] The cobalt-doped ZnO quantum dots were subjected to XRD measurement. The XRD pattern was consistent with Figure 1Similarly, it can be seen that in the crystal structure of cobalt-doped ZnO quantum dots, the 2θ value of the diffraction peak of the ZnO (002) plane is 32.66°; the 2θ value of the diffraction peak of the ZnO (110) plane is 52.59°.

[0101] The cobalt-doped ZnO quantum dots were subjected to high-magnification TEM analysis, and the particle size of the cobalt-doped ZnO quantum dots was approximately 10 nm.

[0102] Example 4

[0103] Preparation of nickel-doped zinc oxide quantum dots (Ni-ZnO)

[0104] (1) Dissolve 5.50 g of Zn(CH3COO)2·2H2O and 0.365 g of nickel acetate in 150 mL of anhydrous ethanol solution and reflux with stirring at 80°C in a water bath for 2 h until the solution becomes colorless and transparent;

[0105] (2) Place the above solution in an ice bath, add 20 mL of 1.75 mol / L KOH-ethanol solution dropwise, and stir for 8 hours;

[0106] (3) The solution obtained in step (2) was mixed with n-hexane in a volume ratio of 1:3, and a large amount of white precipitate appeared. The mixture was centrifuged at 4500 r / min for 15 min and vacuum dried at 60° C. to obtain nickel-doped ZnO quantum dots.

[0107] The nickel-doped ZnO quantum dots were subjected to XRD measurement. The XRD pattern was consistent with Figure 1 Similarly, it can be seen that in the crystal structure of nickel-doped ZnO quantum dots, the 2θ value of the diffraction peak of the ZnO (002) plane is 31.96°; the 2θ value of the diffraction peak of the ZnO (110) plane is 57.89°.

[0108] The nickel-doped ZnO quantum dots were subjected to high-magnification TEM analysis, and the particle size of the nickel-doped ZnO quantum dots was approximately 10 nm.

[0109] Test Example 1

[0110] The metal-doped zinc oxide quantum dots prepared in Examples 1-4 and the zinc oxide quantum dots prepared in Comparative Example 1 were tested as catalysts to determine their catalytic activity, CO selectivity, and the proportion of regulated syngas when catalyzing the electrochemical reduction reaction of carbon dioxide to generate syngas.

[0111] The test conditions are: the actual reaction area is 2cm 2 Electrolysis was performed in a flow electrolysis cell at a constant potential of -0.7 to -1.4 V (vs. RHE reversible hydrogen electrode), with a CO2 gas flow rate of 30 sccm and an electrolyte of 0.5 M KHCO3.

[0112] The test results are as follows Figure 3 , 4 , 5: The Faraday efficiency and syngas ratio of the catalysts before and after doping in the electrochemical reduction of carbon dioxide are compared. The undoped zinc oxide quantum dots obtain a maximum CO Faraday efficiency of 78.4% under -0.9Vvs.RHE conditions, and the syngas ratio can be adjusted between 0.9-3.7 by controlling the potential (between -0.7 and -1.4Vvs.RHE). The selectivity of Cu-ZnO and Fe-ZnO for CO is significantly lower than that of ZnO. The former has a CO Faraday efficiency of 68.4% under -0.9Vvs.RHE conditions, and the syngas adjustment range is also reduced to 0.6-2.2, while the latter has a CO Faraday efficiency of 64.9% under -0.9Vvs.RHE conditions, and the syngas adjustment range is also reduced to 0.8-1.8. The zinc oxide quantum dots doped with Co and Ni enhance the selectivity for CO. The CO Faraday efficiency of Co-ZnO reaches 89.9% under -0.9 V vs. RHE conditions, and the synthesis gas regulation range is also increased to 1.3-9.

[0113] It can be seen from the above embodiments and test examples that by doping zinc oxide quantum dot catalysts with metal elements, the proportion of synthesis gas can be regulated within a relatively large range, so as to facilitate the synthesis of downstream products of the synthesis gas.

[0114] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any appropriate manner, but these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A metal-doped zinc oxide quantum dot catalyst, characterized in that: Based on the total weight of the metal-doped zinc oxide quantum dot catalyst, the metal-doped zinc oxide quantum dot catalyst contains 95-100wt% of zinc oxide and 1-5wt% of doped metal; and the zinc oxide and the doped metal exist in the form of a solid solution.

2. The catalyst according to claim 1, wherein The crystal structure of the metal-doped zinc oxide quantum dot catalyst satisfies the following relationship: 0°<|A 110 -B 110 ∣≤1.8°, where A 110 and B 110 Respectively represent the 2θ value of the diffraction peak of the (110) plane of ZnO in the XRD spectrum of the metal-doped zinc oxide quantum dot catalyst and the XRD spectrum of zinc oxide obtained under the same XRD measurement conditions; 0°<∣A 002 -B 002 ∣≤1.8°, where A 002 and B 002 Respectively represent the 2θ value of the diffraction peak of the (002) plane of ZnO in the XRD spectrum of the metal-doped zinc oxide quantum dot catalyst and the XRD spectrum of zinc oxide obtained under the same XRD measurement conditions.

3. The catalyst according to claim 1 or 2, wherein The doping metal is selected from transition metals, preferably one or more selected from copper, iron, cobalt and nickel.

4. The catalyst according to any one of claims 1 to 3, wherein The average particle size of the metal-doped zinc oxide quantum dot catalyst is 3-15 nm.

5. A method for preparing a metal-doped zinc oxide quantum dot catalyst, characterized in that: The method includes: (1) dissolving a zinc salt and a metal salt in an alcohol solvent to obtain a mixed solution I; (2) reacting the mixed solution I with an alcohol solution of an alkali to obtain a mixed solution II; (3) The mixed solution II is mixed with a solvent and treated to obtain the metal-doped zinc oxide quantum dot catalyst.

6. The preparation method according to claim 5, wherein: In step (1), the mass ratio of zinc salt to metal salt is 1:0.0056-0.0754.

7. The preparation method according to claim 5 or 6, wherein: In step (1), the metal salt is selected from transition metal salts, preferably one or more selected from copper acetate, iron acetate, cobalt acetate and nickel acetate; and / or, the zinc salt is Zn(CH3COO)2·2H2O; And / or, the alcohol solvent is ethanol.

8. The preparation method according to any one of claims 5 to 7, wherein: In step (1), the dissolving temperature is 80-90°C.

9. The preparation method according to any one of claims 5 to 8, wherein: In step (2), the mass ratio of the zinc salt to the base is 1:0.356-0.374; And / or, during the reaction, the alcohol solution of the base is added dropwise, preferably at a rate of 2-10 mL / min; And / or, the base is KOH.

10. The preparation method according to any one of claims 5 to 9, wherein: In step (3), the volume ratio of the mixed solution II to the solvent is 1:3-5; And / or, the solvent is n-hexane.

11. The preparation method according to claim 10, wherein: In step (3), the treatment process includes: centrifuging the mixed product at a speed of 4500-6000 r / min and vacuum drying.

12. A metal-doped zinc oxide quantum dot catalyst obtained by the preparation method according to any one of claims 5 to 11.

13. Use of the metal-doped zinc oxide quantum dot catalyst according to any one of claims 1 to 4 and 12 in the electrochemical reduction reaction of carbon dioxide.

14. A method for preparing synthesis gas from carbon dioxide, characterized in that: The method comprises: in the presence of the metal-doped zinc oxide quantum dot catalyst as described in any one of claims 1 to 4 and 12, electrochemically reducing carbon dioxide and water to obtain synthesis gas.

Citation Information

Patent Citations

  • Macro preparation method for carbon doped zinc oxide-based visible-light catalyst

    CN104148047A

  • Zinc oxide film and preparation method thereof, and light emitting device

    CN109698113A

  • Molybdenum disulfide nanoflower-loaded zinc oxide quantum dot and application thereof in synthesis ammonia electrocatalyst

    CN113235126A

  • Method for preparing multi-carbon product by electrocatalytic conversion of carbon dioxide

    CN115928137A

  • Greening management apparatus based on internet of things and system comprising the same

    KR1020200050856A